Effect of crosswinds and wheel selection on the aerodynamic behavior of a cyclist - Barry, N.; Burton, D.; Crouch, T.; Sheridan, J.; Luescher, R. (Procedia Engineering, 2012)
This paper reports aerodynamic testing results of various styles of bicycle wheels across yaw angles of 0 to 30 degrees. Wheels considered include disc wheels, a bladed spoke wheel and various depth dished wheels. Testing has been completed in a three quarter open jet test section wind tunnel with a anthropomorphic mannequin and rotating front and rear wheels. Data is provided as to the influence of the wheel type on the overall drag and side force, and yaw and roll moment of the rider and bicycle combination. The results demonstrate that the wheel type has a significant effect on both the aerodynamic drag and stability of the bicycle system, and that evaluation of wheel aerodynamic performance should not be based on drag alone.